Evaluation of Microsatellite Instability via High-Resolution Melt Analysis in Colorectal Carcinomas - Thais Maloberti; Sara Coluccelli; Viviana Sanza; Elisa Gruppioni; Annalisa Altimari; Stefano Zagnoni; Lidia Merlo; Antonietta D’Errico; Michelangelo Fiorentino; Daniela Turchetti; Sara Miccoli; Giovanni Tallini; et al. (Journal of Molecular Pathology)
Background/Objectives: Colorectal cancer (CRC) is the third leading cause of cancer death globally, with rising incidence. The immunohistochemistry (IHC) for mismatch repair (MMR) proteins is the first technique used in routine practice to evaluate an MMR status. Microsatellite instability (MSI) may be tested in case of doubt during IHC staining. This study introduces a novel high-resolution melt (HRM) protocol for MSI detection and compares it with traditional fragment length analysis (FLA) via capillary electrophoresis. Methods: A total of 100 formalin-fixed and paraffin-embedded CRC specimens were analyzed using two distinct protocols: one based on FLA (TrueMark MSI Assay kit) and another one based on HRM (AmoyDx® Microsatellite Instability Detection Kit). Results: Overall, 68 (68.0%) of the cases were MSS, and 32 (32.0%) were MSI-H. HRM analysis was first successfully carried out in all the cases. A perfect concordance in MSI evaluation between HRM and FLA was observed. HRM showed slightly shorter hands-on time and turnaround time. Conclusions: We provided evidence of the validity of this new HRM approach in determining the MSI status of colorectal carcinomas.